Analisis Profesionalisme Anggota DPRD dalam Pelaksanaan Fungsi Legislasi di Kota Depok - Muh. Kadarisman (Jurnal Hukum IUS QUIA IUSTUM, 2013)
This research is aimed to analyze the professionalism of legislative member at regional level in Depok in the implementation of legislative function. It uses a descriptive method using the empirical law approach. The result of the research shows that: first, professionalism of the legislative members related to their legislative function has well run as reflected from the performance supported by sufficient science, commitment for the promise, respect to social values, being obedient for the regulations, dedication to public interest, being persistent in following the development of science he or she focuses on, being skillful in problem-solving and controlling the local government well. Second, the implementation of legislative function runs well both in the implementation of representative function, prompting a responsive local regulation, and debate function that is maximally done.